Tracing structural changes in energy materials: A novel multi sample capillary setup for in house powder X‐ray diffraction - Stüble, Pirmin; Binder, Joachim R.; Geßwein, Holger (Electrochemical science advances, 2022)
Lithium ion batteries (LIBs) are currently a major subject of applied electrochemical research as there is a fast growing demand of electrochemical energy storage, driven by the transformation of the automotive sector and the expansion of renewable energies. One of the key strategies to improve LIBs is the optimization of the cathode active materials (CAMs). Therefore, in order to find structure property relations, both crystallographic and electrochemical properties need to be investigated and well understood. However, standard laboratory powder X‐ray diffraction (PXRD) possibly comes to its limit when minor structural variations such as atomic defects, cation order, or minor impurity phases are addressed. In order to focus on such minor structural changes and to find decisive differences in crystalline properties of battery materials, a multi‐sample capillary setup for a multipurpose in‐house PXRD setup was developed. The latter is made up from a six‐circle diffractometer, a microfocus molybdenum rotating anode, and a 2D area detector. The capillary spinner itself is made from commercial components and simple custom‐made adapters. A goniometer head is installed on a rotary module and sample spinning is enabled by a 12 V gear motor. Mounted on a xyz‐stage of the diffractometer, the position of the rotating capillary exposed to the primary beam can be varied while remaining perfectly aligned in the center of the diffractometer. Hence, by packing up to 10 different powder samples separated from each other into a single glass capillary, subsequent measurements of all samples can be carried out without remounting or readjustment. Within a series of samples, the setup is extremely reliable, precise, and accurate, while errors originating from sample displacement, misalignment, or calibration are minimized.